Towards Semantic-Web Based Representation and Harmonization of Standard Meta-data Models for Clinical Studies - Tao, Cui (American Medical Informatics Association, 2011)
In this paper, we introduce our case studies for representing clinical study meta-data models such as the HL7 Detailed Clinical Models (DCMs) and the ISO11179 model in a framework that is based on the Semantic-Web technology. We consider such a harmonization would provide computable semantics of the models, thus facilitate the model reuse, model harmonization and data integration.1